Design and development of a mechanical mixer for talc-based bio control agents - ANJALI V.L SARI A.K WILSON D'SOUZA; Er. Suma Nair (Guide) (Tavanur 2014 DEPARTMENT OF FARM POWER MACHINERY AND ENERGY)
Design and development of a mechanical mixer for talc-based bio control agents
Design and development of a mechanical mixer for talc-based bio control agents